2019
DOI: 10.3389/fonc.2019.00862
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of OTUD7B (Cezanne) Promotes Tumor Progression via AKT/VEGF Pathway in Lung Squamous Carcinoma and Adenocarcinoma

Abstract: OTUD7B, a multifunctional deubiquitinylase, plays an essential role in inflammation and proliferation signals. However, its function in lung cancer remains largely unknown. The aim of this study was to evaluate the prognostic significance of OTUD7B in patients with lung adenocarcinoma and squamous carcinoma and to characterize its molecular mechanisms in lung cancer progression and metastasis. Two tissue microarrays containing 150 pairs of lung squamous carcinoma and matched adjacent non-cancer tissues, and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Instead, OTUD7B is a good indicator for appropriately selecting patients for LCL161 treatment. A recent study showed that OTUD7B regulated invasion and migration via AKT pathway in lung cancer cells [34]. We found that there was no significant change in p-Akt and Akt after LCL161 treatment in both EV and OTUD7B overexpressed H1299 cells ( Figure S1d).…”
Section: Discussionmentioning
confidence: 57%
“…Instead, OTUD7B is a good indicator for appropriately selecting patients for LCL161 treatment. A recent study showed that OTUD7B regulated invasion and migration via AKT pathway in lung cancer cells [34]. We found that there was no significant change in p-Akt and Akt after LCL161 treatment in both EV and OTUD7B overexpressed H1299 cells ( Figure S1d).…”
Section: Discussionmentioning
confidence: 57%
“…OTUD7B (OTU deubiquitinase 7B), also known as CEZANNE , encodes a multifunctional deubiquitinylase enzyme that is essential in inflammation and proliferation signals. Its increased expression has been reported in lung squamous carcinoma and adenocarcinoma compared to normal tissue; in the same cancer model, OTUD7B promoted cell proliferation, migration and metastasization [ 45 ]. Moreover, a lncRNA-miRNA-mRNA axis promoting tumor progression and involving OTUD7B has been reported in pancreatic cancer [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has repeatedly shown that OTUD7B is overexpressed and hold the vital role in in various types of cancers progress including hepatocellular carcinoma [21, 22] lung adenocarcinoma [23, 24], Breast [25], squamous cell carcinoma [26]. In addition, OTUD7B as a crucial immune regulator of NF-KB pathway involving Zap70 and TRAF3 deubiquitination and stabilization [27, 28].…”
Section: Discussionmentioning
confidence: 99%